A typology of masspersonal information seeking repertoires (MISR): Global implications for political participation and subjective well-being. (September 2021) - Liu, James H; Zhang, Robert Jiqi; Vilar, Roosevelt; Milojev, Petar; Hakim, Moh. Abdul; de Zúñiga, Homero Gil; Schumann, Sandy; Páez, Dario
Masspersonal information seeking repertoires are a person-centered method of gaining insight into the relationship between Internet use, subjective well-being, and political participation. Through latent profile analysis, three person types were identified in two waves of stratified samples in 18 countries ( N = 8352). In accord with the "augmentation hypothesis, " high levels of interpersonal contact and traditional mass media usage covaried with high Internet use for the highly engaged type, that had highest political participation and life satisfaction, political knowledge, low depressive symptoms and also high anxiety. The other two types fit the "displacement hypothesis, " where Internet-based media displaces traditional media and face-to-face communication. Compared with the digitally immersed, the traditional repertoire was more knowledgeable and politically engaged, and had better well-being. Latent transition analysis showed these repertoires were stable over 6 months. Identifying different types of people with different information seeking styles clarifies mixed results on effects of online mass media use.